Effect of Disperse Silica on Bound Water in Frozen Cellular Suspensions - Turov, V. V.; Gorbik, S. P.; Chuiko, A. A. (Problems of Cryobiology and Cryomedicine, 2002)
Using the 1H NMR method under conditions of liquid phase freezing-out the effect of disperse silica on hydration rate of model cell suspensions in varying the concentration of cell mass within the range of 0-25% mass and that of SiO2Â within the range of 0â€‘5%Â (w/w) have been studied. Disperse silica was found to cause a strong decrease in bound water concentration in the system. The maximum reduction in inter-phase energy of cell/water (Î³S) was equal to 130 J/g. In concentrated cell suspension the cells and particles of silica can form complex colloid systems with the value ofÂ Î³S in two times lower than that in the binary system. Â